Multiferroic Memories - Amritendu Roy; Rajeev Gupta; Ashish Garg (Advances in Condensed Matter Physics)
Multiferroism implies simultaneous presence of more than one ferroic characteristics such as coexistence of ferroelectric and magnetic ordering. This phenomenon has led to the development of various kinds of materials and conceptions of many novel applications such as development of a memory device utilizing the multifunctionality of the multiferroic materials leading to a multistate memory device with electrical writing and nondestructive magnetic reading operations. Though, interdependence of electrical- and magnetic-order parameters makes it difficult to accomplish the above and thus rendering the device to only two switchable states, recent research has shown that such problems can be circumvented by novel device designs such as formation of tunnel junction or by use of exchange bias. In this paper, we review the operational aspects of multiferroic memories as well as the materials used for these applications along with the designs that hold promise for the future memory devices.